Inactivated vaccine Covaxin/BBV152: A systematic review - Ahmed, Tousief Irshad; Rishi, Saqib; Irshad, Summaiya; Aggarwal, Jyoti; Happa, Karan; Mansoor, Sheikh (Frontiers in Immunology, 2022)
We systematically reviewed and summarized studies focusing on Bharat Biotech’s Whole Virion Inactivated Corona Virus Antigen BBV152 (Covaxin), which is India’s indigenous response to fighting the SARS-CoV-2 pandemic. Studies were searched for data on efficacy, immunogenicity and safety profile of BBV152. All relevant studies published upto March 22, 2022 were screened from major databases and 25 studies eventually inducted into the systematic review. The studies focused on the virus antigen (6 μg) adjuvanted with aluminium hydroxide gel and/or Imidazo quinolin gallamide (IMDG), aTLR7/8 agonist. Pre-clinical,phase I and II clinical trials showed appreciable immunogenicity. Both neutralizing and binding antibody titers were significant and T cell responses were Th1-biased. Phase III trials on the 6 μg +Algel-IMDG formulation showed a 93.4% efficacy against severe COVID-19. Data from the trials revealed an acceptable safety profile with mostly mild-moderate local and systemic adverse events. No serious adverse events or fatalities were seen and most studies reported milder and lesser adverse events with Covaxin when compared with other vaccines, especially Oxford-Astra Zeneca’s AZD1222 (Covishield). The immunogenicity performance of Covaxin, which provided significant protection only after the 2nd dose, was mediocre and it was consistently surpassed by Covishield. One study reported adjusted effectiveness against symptomatic infection to be just 50% at 2 weeks after the 2nd dose. Nonetheless, appreciable results were seen in previously infected individuals administered both doses. There was some evidence of coverage against the Alpha, Beta, and Delta variants. However, neither Covaxin nor Covishield showed sufficient protection against the Omicron variant. Two studies reported super-additive results on mixing Covaxin with Covishield. Fand further exploration of heterologous prime-boost vaccination with a combination of an inactivated vaccine and an adenoviral vector-based vaccine for tackling future variants may be beneficial.